High Mobility Group Proteins in Sepsis - Liang, Guibin; He, Zhihui (Frontiers in Immunology, 2022)
Sepsis, a systemic inflammatory response disease, is the most severe complication of infection and a deadly disease. High mobility group proteins (HMGs) are non-histone nuclear proteins binding nucleosomes and regulate chromosome architecture and gene transcription, which act as a potent pro-inflammatory cytokine involved in the delayed endotoxin lethality and systemic inflammatory response. HMGs increase in serum and tissues during infection, especially in sepsis. A growing number of studies have demonstrated HMGs are not only cytokines which can mediate inflammation, but also potential therapeutic targets in sepsis. To reduce sepsis-related mortality, a better understanding of HMGs is essential. In this review, we described the structure and function of HMGs, summarized the definition, epidemiology and pathophysiology of sepsis, and discussed the HMGs-related mechanisms in sepsis from the perspectives of non-coding RNAs (microRNA, long non-coding RNA, circular RNA), programmed cell death (apoptosis, necroptosis and pyroptosis), drugs and other pathophysiological aspects to provide new targets and ideas for the diagnosis and treatment of sepsis.